Factors influencing lecturers' organizational commitment in higher education: a systematic literature review - Chen, Shenquan; Abdul Kadir, Suhaida; Mohd Sufian Kang, Enio Kang (Sciedu Press, 2024)
This paper analyzes 30 research articles published between 2018 and 2024 through a systematic literature review methodology to explore the multidimensional factors that influence organizational commitment among higher education lecturers. The research focused on individual subjective factors such as gender, age, emotional intelligence, personal values and beliefs, self-efficacy, career satisfaction, mental health status, and external environmental factors, including leadership style, managerial effectiveness, organizational support, and work environment. In addition, the article provides an in-depth examination of socio-cultural factors, such as societal values towards education, family support, and social support, and how these factors combine to contribute to lecturers' organizational commitment. The article reveals the complex interactions between these factors and highlights the joint importance of personal and external factors in shaping lecturers' organizational commitment. The findings of this study not only provide practical strategies for educational administrators to enhance lecturers' organizational commitment and point to the need for future research to consider wider cultural and geographical differences to contribute to the overall improvement of educational quality and teaching effectiveness.